ENHANCING BIBLIOMETRIC ANALYSIS SKILLS OF INFORMATION TECHNOLOGY STUDENTS THROUGH PUBLISH OR PERISH TRAINING - Adinugraha, Hendri Hermawan; Sofia, Lailatul; Andrean, Rizky (PT. ANAN PUBLISHER CENDEKIA, 2025)
Bibliometric literacy skills are essential in supporting students’ academic quality, especially in preparing scientific papers based on citation data. The facts show that UIN Gusdur Information Technology Study Program students still face obstacles in optimally understanding and applying the basic principles of bibliometric analysis. This community service activity aims to improve students’ ability to search, evaluate, and interpret scientific literature using the Publish or Perish application. The methods used in this activity include socialization, education, and practical seminars, which are carried out offline for three days. The pre-test and post-test results showed significant improvements in understanding bibliometric concepts, mastery of applications, and the ability to compile references based on citation data. Most participants also showed high enthusiasm and interest in developing these skills independently. This activity indicates that the Publish or Perish training is a practical and innovative educational approach in strengthening students’ academic literacy. The findings support integrating bibliometric training into the curriculum or broader academic development programs. Further work is recommended to examine the long-term impact of this training on students’ scientific publication productivity in various disciplines.